Pengaruh Ukuran Perusahaan, Likuiditas, Risiko Bisnis, dan Profitabilitas Terhadap Nilai Perusahaan - Fitria Dewi; Novera Kristianti Maharani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to empirically evaluate how firm size, liquidity, business risk and profitability affect firm value. The independent variables in the study consist of firm size using the natural logarithm proxy of total assets, liquidity using the Current Ratio proxy, business risk using the natural logarithm proxy of the standard deviation of earnings before interest and tax (EBIT), and profitability using the Return on Equity proxy. Firm value is determined as the dependent variable using the Price Book Value proxy. Using purposive sampling technique, there are 13 companies as samples from a population of 20 health companies listed on the IDX from 2020 to 2023. Multiple liner regression analysis was used to test secondary data from financial reports, as well as the company's annual report. Partially, firm size and liquidity are not indicated to affect firm value, while business risk and profitability have a positive influence on firm value.